Settlement of Thick Clay Deposits under Piled-Raft Foundation and Design Considerations (Pile Dimensions) - Lee Kwang Yeol (Institute of Research and Community Outreach - Petra Christian University, 2015)
Characteristics and histories of the deltaic deposits in geotechnical perspective are studied. Geotechnical issues of clay deposits under floating foundation systems also analyzed. Theoretical expressions and parameters were examined by an experimental study and numerical analysis on the laboratory scales and field measurement in this study. Also, piled raft foundation on thick clay deposits is designated to optimize pile configuration. The predictions of settlements of piled rafts foundation are proposed based on pile dimensions by utilizing a normalized Ap/nL and Bg/Br. Practical design of piled raft foundations is made for the light bridges and five story buildings on thick clay deposits to discuss the long-term settlement, and it is found that the piled raft is well applicable and effective on thick clay deposits, and that differential settlements of the foundation should be managed by designing the configuration of pile lengths and spacing.